A Comparative Analysis of Air Quality between Taiwan and South Korea - Darmansyah, .; Meghan, Jonathan; Nur Novilina, Arifianingsih; Indah Suci, Ramadhani; Ahmad Daudsyah, Imami; Moondra, Zubir; Siti Rahmah, .; I. Wayan Koko, Suryawan; Rachmat, Mulyana; Wisnu, Prayogo (INTI International University, 2023)
Until now, there has been no research that uses a monitoring method approach that is easily accessible and costless using TAQMN. This study aimed to determine the air quality of Zhongli District (Taiwan), which we then compare with Incheon Metropolitan City (South Korea). These two regions have different characteristics in terms of population and territorial designation. From February 27 to March 8 of 2022, pictures of the Zhongli skyline were captured every morning at 9 a.m. at the Re Cheng-hall student dormitory of Chung Yuan Christian University. Additionally, the Zhongli skyline photo findings are contrasted with the information provided by TAQMN's air quality index monitoring system. Overall, the air quality index in Zhongli District is better than Taipei City in the same period. The air quality index (AQI) for the Zhongli area ranged between 45 and 121, where the period's median AQI was 57. Other significant variables include PM2.5 and PM10 values of 14 g/m3 , 20 g/m3 respectively. Overall, the air quality index in Zhongli district Taoyuan city in Taiwan is better than Incheon city in South Korea on the same period. The average AQI in Incheon varies from 58 to 124 over the course of a 24-hour period